2023
DOI: 10.1002/adsu.202300305
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium Composites for Sustainable Development in Developing Countries: The Case for Africa

Stefania Akromah,
Neha Chandarana,
Stephen J. Eichhorn

Abstract: The socio‐economic struggles in Africa are partly attributed to the low productivity of the agricultural sector. The Sustainable Development Goals Centre for Africa (SDGC/A) and the African Development Bank Group (AfDBG) both agree that the continent needs sustainable interventions to boost agricultural productivity, employment, and income. In this regard, mycelium composite production can present one potential solution. The added value to agricultural waste used to produce mycelium composites can generate add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 175 publications
1
10
0
Order By: Relevance
“…These findings align with the theory of earlier studies on MBC production, indicating that the tensile strength of MBCs is influenced by various factors associated with substrate type, mycelium binder network structure, and the pressing process [ 30 , 41 , 44 , 67 ]. Generally, the particle size and structure of each substrate material can impact the porosity and overall structure of MBCs, thereby influencing tensile strength and other mechanical properties [ 79 ].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These findings align with the theory of earlier studies on MBC production, indicating that the tensile strength of MBCs is influenced by various factors associated with substrate type, mycelium binder network structure, and the pressing process [ 30 , 41 , 44 , 67 ]. Generally, the particle size and structure of each substrate material can impact the porosity and overall structure of MBCs, thereby influencing tensile strength and other mechanical properties [ 79 ].…”
Section: Resultssupporting
confidence: 90%
“…The pressing action caused differences in the mechanics between the fungal mycelium and substrate, which improved the MBCs elasticity and strength [ 24 , 30 ]. Additionally, prior research suggested that density plays a role, with higher density often correlating with increased bending strength, although there may be trade-offs with other properties like weight and porosity [ 44 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Ghana, this model assumes that the MCB production facility is located near the Crop Research Institute of the Council of Scientific & Industrial Research (CSIR) in the Ejura-Sekyedumase district (Ashanti region), one of the major agricultural hubs of the country 19 . This location provides both an abundant biomass reserve as well as scientific research support, which, as suggested in our previous review 10 , can be valuable for the establishment and expansion of the MC technology in Africa.…”
Section: Goal and Scope Definitionmentioning
confidence: 93%